Kesalahan Berbahasa pada Berita Daring/Online - Nurcaya Nurcaya; Ahmad Ghazali Samad; Rudi Karma; Dirga Jaya (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstrac: Language Errors in Online News. This research was motivated by the findings of language errors found in news writing, especially in online news. Online news is news that utilizes the network as a medium of delivery and is considered the fastest in its presentation. This study aims to describe the misuse of Indonesian in writing online news. There are two benefits of this research, namely theoretical benefits and practical benefits. This type of research is qualitative research using descriptive methods. The object of research analyzed in this study is language errors in online news. Furthermore, the source of data in this study is news published in online media. Data collection techniques in this study are divided into several stages, namely reading and observation, checking, then the last is documentation. The results of this study are (1) the form of spelling errors including errors in the use of capital letters, writing italics. use of prepositions, use of periods, use of commas and use of hyphens. (2) Forms of misuse of diction include waste of the suffix "his" and misuse of conjunctions.